1992
DOI: 10.1016/0014-5793(92)80410-i
|View full text |Cite
|
Sign up to set email alerts
|

Cis‐trans isomerization is rate‐determining in the reactivation of denatured human carbonic anhydrase II as evidenced by proline isomerase

Abstract: The refolding of human carbonic anhydrase II is a sequential process. The slowest step involved is the recovery of enzymic activity (t½=9 min). Kinetic data from ‘double‐jump’ measurements indicate that proline isomerization might be rate determining, in the reactivation of the denatured enzyme. Proof of this is provided by the effect of proline isomerase on the reactivation kinetics; the presence of isomerase during reactivation lowers the half‐time or the reaction to 4 min, and inhibition of proline isomeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Recent studies of mutants of human carbonic anhydrase I1 confirmed that cis-trans isomerization of proline is a rate- determining factor in the reactivation of denatured protein (Fransson et al, 1992). Importantly, the more energetically favored trans conformation is adopted in the open form, influencing the equilibrium in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of mutants of human carbonic anhydrase I1 confirmed that cis-trans isomerization of proline is a rate- determining factor in the reactivation of denatured protein (Fransson et al, 1992). Importantly, the more energetically favored trans conformation is adopted in the open form, influencing the equilibrium in that direction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, Fransson et al observed that incorporating PPIase in the refolding reaction mixture of GuHCl-denatured HCA II decreased the half-time of folding from 9 to 4 min and removed the effect of time delay in refolding. 667 Further, the addition of Cyclosporin A, a specific inhibitor of PPIase, 742 completely abolished the observed PPIasemediated acceleration of folding. If PPIase acted efficiently on all peptidyl-Pro bonds, the expected half-time of refolding would decrease to 1 min.…”
Section: Isomerization Of Pro Residuesmentioning
confidence: 95%
“…Proline isomerization is the rate-limiting step in the folding of CA. 667,[680][681][682][683][684] 4. After denaturation with urea, guanidinium hydrochloride (GuHCl), heat, or SDS, CA renatures spontaneously after removal of the denaturant.…”
Section: Ca As a Model Protein For Studying The Denaturation And Renamentioning
confidence: 99%
“…The measurements of the regain in CO 2 hydration activity during refolding were performed as described previously. 14 The concentration of HCA II pwt during refolding was 0.83 lM and the concentration of Cyp18 and Cyp18 R55A was 8.3 lM, and when applicable CsA was added to a concentration of 25 lM. All solutions were buffered with 0.1M Tris-H 2 SO 4 , pH 7.5.…”
mentioning
confidence: 99%